Sensory Profile on Robusta Coffee by Rate-All-That-Apply (RATA) - Belgis, Maria; Zhafirah Arifin, Thalita; Prameswari, Dayintaguna; Taruna, Iwan; Choiron, Miftahul; Witono, Yuli; Dwi Masahid, Ardiyan (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2023)
Coffee flavor strongly influences consumers preference. Geographical location is one factor influencing the flavor of Robusta coffee. Descriptive sensory using RATA was used to differentiate the sensory profiles of several Robusta coffees. Sensomic approach by Principal Component Analysis (PCA) success- fully differentiated Robusta coffee from Jember Regency, East Java, Indonesia. It showed that Robusta from different growing locations has specific sensory characteristics. Robusta coffee from Gunung Malang, Tanggul, and Pakis was characterized by sweet and acid aromas, while coffee from Kemiri was characterized by sweet and sour taste, brown color, bitter aroma, and rough mouthfeel. Meanwhile Sidomulyo I and Sidomulyo II coffees, which were grown near each other and at similar altitudes, have similar characteristics, although the process was different. Both coffees have bitter aftertastes and bodies, burnt aromas, astringent flavors, and high levels of bitterness. In contrast, Robusta Rowosari, Tugusari, and Badean were characterized by low sweetness, sourness, bitter aroma, and rough mouthfeel.